The Use of Self-Correction and Peer-Correction Technique in Enhancing Students’ Writing Skill - Wersi Murtini, Ni Made (Journal on Studies in English Language Teaching (JOSELT), 2024)
This research utilized self-correction and peer-correction techniques on enhancing the writing skills of first-semester students in the English Language Education Study Program. Preliminary observations indicated that many students in semester 1B struggled with writing accuracy and fluency. The study aimed to determine whether the implementation of self-correction and peer-correction techniques could improve these students' writing skills. Conducted as classroom action research, the study was completed in three cycles, with data collected through a series of assessments: pre-test, post-test 1, post-test 2, and post-test 3. The results revealed a significant improvement in the students' mean scores from the pre-test to the post-tests, demonstrating that both correction techniques contributed positively to their writing development. This research concludes that the integration of self-correction and peer-correction effectively enhances students' writing skills, fostering a more accurate and reflective approach to language use.